Good Practice at GASAG Group: Recommendations for the Application of Internal Crowdsourcing from a Business Perspective - Porth, Florian (Springer International Publishing, 2021)
Developing innovative and marketable products and services and maintaining innovation capacity are basic prerequisites for a company’s economic success and present implicit challenges in the adaptation to twenty-first-century needs. These success factors are put at risk by silo mentalities and by insufficiently pronounced cross-departmental knowledge transfers. The GASAG Group as a typical organizational layout of medium-sized enterprises in Germany has been and still is confronted with these challenges as well. In order to face them, the GASAG Group decided to work on company culture as well as to develop an open and innovative mindset, prompting it to join the ICU (ICU stands for ‘Internal Crowdsourcing in Enterprises’ and is a joint project funded by the Federal Ministry of Research and Education (BMBF) and the European Social Fund (ESF) for a period of 3 years, from June 2017 to May 2020, under the funding measure ‘Work in the Digitalised World’ and supervised by the project management organization Karlsruhe. The project goal was the development of an employee-friendly cross-industry reference model for Internal Crowdsourcing.). Research Project in 2017. The aim of this chapter is to describe the ICU approach from the practical, company perspective of the GASAG Group and to map out identified success factors as well as provide general recommendations for the implementation of Internal Crowdsourcing in a business environment.